The Importance of Management Partnerships in Developing Tourism Sustainability After the Covid-19 Pandemic at Taman Impian Jaya Ancol - Awaloedin, Dipa Teruna; Iskandarmouda, Elena Edelweis; Pradini, Gagih (International Journal of Education, Information Technology, and Others, 2024)
Tourism has become a basic need for many people and is considered a human right that should be respected and protected. As an essential sector in the global economy, tourism contributes significantly to national revenue and creates employment opportunities. Taman Impian Jaya Ancol, a major tourist destination in Jakarta, faces various challenges due to the Covid-19 pandemic, including a decline in visitor numbers, increased health costs, and changes in tourist behavior. This study aims to analyze the role of partnerships in building a positive image for Taman Impian Jaya Ancol in the post-pandemic era. Using literature studies and SWOT analysis, this research evaluates internal and external factors affecting this tourist destination. The analysis indicates that partnerships with various stakeholders, including government, local communities, environmental organizations, the private sector, and media, are key strategies to address post-pandemic challenges. Partnerships have proven to offer positive contributions by enhancing security, supporting local economic development, developing sustainable practices, and increasing tourism appeal. However, barriers such as economic uncertainty, increased operational costs, and travel restrictions require adaptive and innovative strategies. Recommendations for strengthening partnerships, including marketing innovation, diversification of funding sources, and collaboration with media and influencers, can help Taman Impian Jaya Ancol rebuild its positive image in the post-pandemic era. The study concludes that partnerships are a critical foundation for overcoming the post-pandemic challenges in the tourism sector. Strategies involving collaboration, innovation, and adaptability are needed to ensure the sustainability of partnerships and the long-term success of Taman Impian Jaya Ancol.